Genetic and physical map of broad host range cosmid pRG930cm - Chibeu,Andrew (Pontificia Universidad Católica de Valparaíso, 2009)
We hereby present the complete sequence and annotation of pRG930cm, a spectinomycin/streptomycin/chloramphenicol-resistant cosmid vector. pRG930cm (17,256 bp; GenBank Accession No.: FM174471) has a broad host range, and is stably maintained by a number of Gram-negative bacteria including Pseudomonas spp, Escherichia coli, Agrobacterium tumefaciens and Azorhizobium caulinodans ORS571. pRG930cm is already widely used and its sequence will aid efficient construction and analysis of cosmid libraries.